The Journey of Humanity and the keys to human progress - Galor, Oded. (London Penguin, 2022)
The stunning advances that have transformed human experience in recent centuries are no accident of history - they are the result of universal and timeless forces, operating since the dawn of our species. Drawing on a lifetime''s scientific investigation, Oded Galor''s ground-breaking new vision overturns a host of long-held assumptions to reveal the deeper causes that have shaped the journey of humanity
Includes index
Keywords: Humanity, History